Oral and topical extra-label administration of fipronil to laying hens: Assessment of the egg residue patterns - Canton, Lucila; Canton, Candela; Ceballos, Laura; Dominguez, Paula; Rodriguez, Jose; Lanusse, Carlos Edmundo; Alvarez, Luis; Moreno, Laura (Wiley, 2021)
This experimental work reproduces the fipronil extra-label administration performed by producers in laying hens. The scientific goal was to characterize the residual concentrations in eggs from treated hens and suggest the withdrawal periods that should be respected to avoid risk for consumers. Thirty-four laying hens were allocated into two groups: Group A was treated with fipronil in feed, two single doses of 1 mg kg-1 day-1 ; Group B was administered a single dose of 1 mg kg-1 by the topical route. Fipronil egg residues were quantified by HPLC-MS/MS. Fipronil and its sulphone metabolite (fipronil-SO2 ) were measured in egg after both treatments. The highest egg residual profile was always for fipronil-SO2 . Mean maximum egg concentrations (Cmax ) of 228.5 ± 79.8 ng/g (fipronil) and 1,849 ± 867 ng/g (fipronil-SO2 ) were found after fipronil administration in feed. The lowest residual levels were quantified after the topical treatment with Cmax of 27.1 ± 4.9 and 163 ± 26 ng/g for fipronil and fipronil-SO2 . Mean fipronil marker residues and established MRLs allowed calculating the withdrawal periods, the shortest being 74 days after topical administration. Such a long withdrawal period is difficult to meet in egg production systems. Thus, the extra-label use of fipronil in laying hens should not be recommended under any circumstances.